The relation of packaging material to the keeping quality of frozen pork - Mackintosh, D. L.; Merkel, R.A.; Hall, J.L.; Harrison, D.L.; Anderson, L. (Kansas Agricultural Experiment Station, 2011)
Fresh pork sausage is used by an increasing number of families with home storage units. Several years of research here indicated that with salt, pepper, and sage added before sausage is stored, its maximum storage life is 6 to 9 months at 0 F, and then only when tested packaging materials are used.
Keywords: Meat; Pork sausage; Storage